PENGARUH SIFAT FISIS DAN MEKANIS DISC BRAKE SETELAH DIPANASKAN 2000 C PADA TRUK UNIMOG - Sukahar; Hafid, Achmad; Suparja (PPM Sdirjianbang Akademi Militer, 2023)
This research is about analysis physical and mechanical character of Truck Unimog disc brake after heated with 2000C. The purpose is considerate for TNI-AD leader specifically for squad the apply and use to overcome the weakness of disc brake. Weighing 7,5 tons, Unimog mobility is fairly high, this truck with 60000 cc capacity engine can through the field very well as towing cannons truck and have reliable power to through altitude and rugged terrain. Common cause frequent fractures until crooked of disc brake part there at time the truck doing mobility with fast and long through time, and when hit by hard object in the field of Indonesia have many rocky terrain, hills, hard soil structure, as well as weakness material of that disc brake. Therefore at the Unimog truck disc brake it will be tested about microstructure, disc brake material composition and hardness. Be based the result of disc brake, evenly this material having hardness value before heated is about 236, 213 kg/mm2 and after heated is 275, 318 kg/mm2 where more and more result has gotten, and then more and more hardness too that material. And in this test a steel disc brake after heating 2000C has a greater value in comparing pre-heated it is clear that the steel brake disc is resistant to heat and friction. so that the future does not happen again broke or bent the brake disc so that it is not an accident or accident that occurred at the time of mobility and the driver can easily operate these vehicles is that the brake disc can work well then the user not to place excessive heat later also necessary maintenance and routine and periodic maintenance of the braking system, especially on the brake lining and brake disc so as to prevent damage to both the brake disc itself or on the vehicle.